The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31219/osf.io/dmksp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is it a Fallacy to Believe in the Hot Hand in the NBA Three-Point Contest?

Abstract: The NBA Three-Point Contest has been considered an ideal setting to study the hot hand, as it showcases the elite professional shooters that hot hand beliefs are typically directed towards, but in an environment that eliminates many of the confounds present in game action. We collect 29 years of NBA Three-Point Contest television broadcast data (1986-2015), apply a statistical approach that improves on those of previous studies, and find considerable evidence of hot hand shooting in and across individuals. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…GVT's betting study on hot hand beliefs, which Gilovich has referred to as "...the most important bit of evidence against the hot hand," found that players are unable to successfully predict the shot outcomes of their teammates. 70 However, it has recently been shown that the statistical tests used in GVT's betting study are severely underpowered, and the effect sizes misinterpreted (Miller and Sanjurjo 2017). In fact, an improved re-analysis of their data yields strong evidence that players are skilled at predicting their teammates' shot outcomes (Miller and Sanjurjo 2017), which is consistent with the results on beliefs what we observe here.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…GVT's betting study on hot hand beliefs, which Gilovich has referred to as "...the most important bit of evidence against the hot hand," found that players are unable to successfully predict the shot outcomes of their teammates. 70 However, it has recently been shown that the statistical tests used in GVT's betting study are severely underpowered, and the effect sizes misinterpreted (Miller and Sanjurjo 2017). In fact, an improved re-analysis of their data yields strong evidence that players are skilled at predicting their teammates' shot outcomes (Miller and Sanjurjo 2017), which is consistent with the results on beliefs what we observe here.…”
Section: Resultssupporting
confidence: 79%
“…Nevertheless, we find a hot hand effect across all extant controlled shooting studies. This evidence is consistent with the pooled hot hand effects observed in relatively less controlled environments such as the ("semi-controlled") NBA three point contest (Miller and Sanjurjo 2015), 69 NBA free throw shooting (Arkes 2010;Yaari and Eisenmann 2011), and NBA live ball shooting (Bocskocsky et al 2014).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…(3) as those for the NBA three-point contest (Miller & Sanjurjo, 2019) and NBA FT shooting (Arkes, 2010(Arkes, , 2013Lantis & Nesson, 2021;Mews & Ötting, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…According to this idea, people assume equal frequency of outcomes within a random sequence that fits into short-term memory (STM), and such sequences have a tendency to alternate too often. A recent account argues that biases of randomness reflect people’s limited perceptual experiences with the environment (Hahn & Warren, 2009; Miller & Sanjurjo, 2015).…”
mentioning
confidence: 99%